Performance evaluation of DC Power Optimizer (DCPO) for Photovoltaic (PV) system during partial shading - Salam, Zainal; Ramli, Mohd zulkifli (Elsevier Ltd., 2019)
One of the drawbacks of the maximum power point tracker (MPPT) algorithm is its inability to extract the energy from partially shaded photovoltaic (PV) panels. This is because the bypass diode short circuits the shaded panel; consequently no power can be extracted from it. However, it is possible to harvest the energy from the shaded panel using dc power optimizer (DCPO)da specialized dc-dc converter that incorporates an independent MPPT controller. This paper analyzes, simulates and evaluates the performance of the PV system with DCPO and to compare it to the conventional system with the bypass diode alone. The field data from a 1.25 kWp system suggests that the cumulative energy gain of DCPO (compared to bypass diode) increases from 2.8 to 6.4%, depending upon the type of shading pattern imposed on the panels. Further, this work investigates the performance of DCPO for sub-module shading. It is found that for a panel that consists of three sub-modules, the energy yield is improved by approximately 1%. With such marginal increase, it may not be justifiable to install one DCPO device for each sub-module of a panel.